2017
DOI: 10.3390/ijerph14020116
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Perceptions of Air Pollution Health Risk: Does Environmental Exposure Matter?

Abstract: This article extends environmental risk perception research by exploring how potential health risk from exposure to industrial and vehicular air pollutants, as well as other contextual and socio-demographic factors, influence racial/ethnic differences in air pollution health risk perception. Our study site is the Greater Houston metropolitan area, Texas, USA—a racially/ethnically diverse area facing high levels of exposure to pollutants from both industrial and transportation sources. We integrate primary hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Some work has shown racial/ethnic and neighborhood‐level differences in perceived risk (Adeola ; Macias ; Vaughan and Nordenstam ), though the direction of this relationship is unclear and depends on the environmental hazard in question (Adeola ; Mohai and Bryant ). In general, some of this work has shown that the more advantaged segments of society perceive lower environmental risks (Chakraborty et al ; Finucane et al ; Flynn, Slovic, and Mertz ), which is fitting with the work on objective indicators.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 61%
See 1 more Smart Citation
“…Some work has shown racial/ethnic and neighborhood‐level differences in perceived risk (Adeola ; Macias ; Vaughan and Nordenstam ), though the direction of this relationship is unclear and depends on the environmental hazard in question (Adeola ; Mohai and Bryant ). In general, some of this work has shown that the more advantaged segments of society perceive lower environmental risks (Chakraborty et al ; Finucane et al ; Flynn, Slovic, and Mertz ), which is fitting with the work on objective indicators.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 61%
“…However, the vast majority of these studies measure neighborhood‐level environmental hazards using objective indicators, such as the locations of industrial polluters or Environmental Protection Agency (EPA) data on air quality (Bravo et al ; Jones et al ). Considerably fewer studies have been conducted on the case of perceived environmental exposure, especially at the neighborhood level, which is the focus of the present study (Chakraborty et al ). Some work has shown racial/ethnic and neighborhood‐level differences in perceived risk (Adeola ; Macias ; Vaughan and Nordenstam ), though the direction of this relationship is unclear and depends on the environmental hazard in question (Adeola ; Mohai and Bryant ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The existing literature suggests that ecological attitudes directly affect ecological protection behavior [19,40]. However, no literature reveals the intermediate mechanism between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Although experts and public bodies recognize the effects of air pollution on public health, individuals do not always adequately understand these links (Chakraborty, Collins, Grineski, & Maldonado, 2017;Johnson, 2002). Therefore, perceptions of severity and susceptibility to the health effects of air pollution vary significantly across individuals and settings (Bickerstaff & Walker, 2001;Oltra & Sala, 2016).…”
Section: Public Perception Of Air Qualitymentioning
confidence: 99%